2017
DOI: 10.1002/cne.24319
|View full text |Cite
|
Sign up to set email alerts
|

Thorny ganglion cells in marmoset retina: Morphological and neurochemical characterization with antibodies against calretinin

Abstract: In primates, over 17 morphological types of retinal ganglion cell have been distinguished by their dendritic morphology and stratification, but reliable markers for specific ganglion cell populations are still rare. The calcium binding protein calretinin is known to be expressed in the inner nuclear and the ganglion cell layer of marmoset retina, however, the specific cell type(s) expressing calretinin in the ganglion cell layer are yet to be determined. Here, we identified calretinin positive retinal ganglion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…The potential cross-reactivity of the rabbit calbindin antiserum with calretinin could explain the fact that in marmoset we found ganglion cells among the injected cells when the antiserum was used at a higher concentration. In favor of this hypothesis, the injected ganglion cells resembled previously identified calretinin expressing thorny ganglion cells (Chandra et al, 2017). Likewise, the fact that in marmoset ON ChAT cells were labeled with the rabbit calbindin antiserum but not the mouse calbindin antibody may be explained by cross-reactivity, if one assumes that marmoset ON ChAT cells express calretinin but not calbindin.…”
Section: Antibody Comparisonmentioning
confidence: 59%
See 2 more Smart Citations
“…The potential cross-reactivity of the rabbit calbindin antiserum with calretinin could explain the fact that in marmoset we found ganglion cells among the injected cells when the antiserum was used at a higher concentration. In favor of this hypothesis, the injected ganglion cells resembled previously identified calretinin expressing thorny ganglion cells (Chandra et al, 2017). Likewise, the fact that in marmoset ON ChAT cells were labeled with the rabbit calbindin antiserum but not the mouse calbindin antibody may be explained by cross-reactivity, if one assumes that marmoset ON ChAT cells express calretinin but not calbindin.…”
Section: Antibody Comparisonmentioning
confidence: 59%
“…In contrast, in mouse retina, calbindin-positive cells include a variety of ganglion cell types and make up about 20% of the ganglion cell population (Gu et al, 2016). Species-related differences in the expression of calcium-binding proteins by ganglion cells have been observed previously, e.g., in human retina, calretinin is expressed by two populations of bistratified ganglion cells (Lee et al, 2016), whereas in marmoset calretinin is expressed by thorny ganglion cells (Chandra et al, 2017). Whether these differences are correlated with functional differences will need to be determined.…”
Section: Calbindin Immunoreactivity In Ganglion Cellsmentioning
confidence: 85%
See 1 more Smart Citation
“…In marmoset retina, the large majority of Satb2 expressing ganglion cells were classified as broad thorny cells (Figure 14(a)). Broad thorny as well as narrow thorny cells in marmoset retina have previously been shown to express the calcium binding protein calretinin (Chandra et al, 2017) suggesting that calretinin and Satb2 are co‐expressed in a population of ganglion cells. Thus, we processed a piece of marmoset retina with antibodies against Satb2 (mouse), calretinin, and RBPMS (Figure 18).…”
Section: Resultsmentioning
confidence: 99%
“…As discussed in that study, the different types can be distinguished based on their dendritic field size, morphology, and stratification in the inner plexiform layer. Briefly, broad thorny cells have a dense dendritic tree and stratify broadly in the inner plexiform layer; narrow thorny cells stratify narrowly in either ON or OFF sublamina (see also Chandra, Lee, & Grünert, ), whereas large bistratified cells have sparse dendritic trees stratifying in both ON and OFF sublamina. Based on these criteria we found that both PIm, as well as SC injections, revealed a variety of widefield retinal ganglion morphological cell types.…”
Section: Resultsmentioning
confidence: 99%